Escaping the Nuclear Confines: Signal-Dependent Pre-mRNA Splicing in Anucleate Platelets - Denis, Melvin M.; Tolley, Neal D.; Bunting, Michaeline; Schwertz, Hansjörg; Jiang, Huimiao; Lindemann, Stephan; Yost, Christian C.; Rubner, Frederick J.; Albertine, Kurt H.; Swoboda, Kathryn J.; Fratto, Carolyn M.; Tolley, Emilysa; et al. (Cell, 2005)
Platelets are specialized hemostatic cells that circulate in the blood as anucleate cytoplasts. We report that platelets unexpectedly possess a functional spliceosome, a complex that processes pre-mRNAs in the nuclei of other cell types. Spliceosome components are present in the cytoplasm of human megakaryocytes and in proplatelets that extend from megakaryocytes. Primary human platelets also contain essential spliceosome factors including small nuclear RNAs, splicing proteins, and endogenous pre-mRNAs. In response to integrin engagement and surface receptor activation, platelets precisely excise introns from interleukin-1β pre-mRNA, yielding a mature message that is translated into protein. Signal-dependent splicing is a novel function of platelets that demonstrates remarkable specialization in the regulatory repertoire of this anucleate cell. While this mechanism may be unique to platelets, it also suggests previously unrecognized diversity regarding the functional roles of the spliceosome in eukaryotic cells.